أثر صيغ التمويل الإسلامي القائمة على الهامش على المردودية المالية للمؤسسات الاقتصادية -دراسة قياسية -2020- لعينة من المؤسسات الاقتصادية المدرجة في السوق المالي السعودي خلال الفترة 2012: The impact of Islamic financing formulas based on margin on the financial profitability of the economic institutions - An empirical study of a sample of economic institutions listed in the Saudi financial market during the period 2012-2020- - حبار عماد الدين,; متناوي امحمد, (Journal of North African Economies, 2025)
This study aims to highlight the impact of the Islamic financing formulas based on the margin on the financial profitability of a sample of the economic institutions listed in the Saudi financial market, by analyzing the panel data for the study variables using the Eviews program. 12, Where the study dealt with a set of concepts related to financial leverage, financial profitability, Islamic financing formulas and the method of calculating their cost, The study concluded that there is a positive and statistically significant impact only of long-term Islamic financing formulas based on margins on the financial profitability For the economic institutions that represent the study sample